Comparative immunological roles of TEP1 in Anopheles gambiae and Biomphalaria glabrata: implications for malaria and schistosomiasis control - Li, Hongyu; Feng, Yilu; Qian, Yuncheng; Jiang, Wenjie; Zhu, Yunhuan; Xu, Jialu; Li, Xianwei; Fei, Xinyi; Wang, Ruke; Shao, Yuqing; Du, Lailing; Zhang, Xiaofen; et al. (Frontiers in Immunology, 2025)
Malaria and schistosomiasis represent two of the most significant global parasitic diseases in terms of public health burden. These diseases are transmitted through Anopheles mosquitoes and freshwater snails, respectively. Although their transmission mechanisms differ, both pathogens critically interact with thioester-containing proteins (TEPs) during immune evasion and clearance within their invertebrate hosts. This review compares the activation mechanisms and functional divergences of TEPs in Anopheles gambiae and Biomphalaria glabrata in the context of host anti-infective immunity. We focus on the roles of AgTEP1 and BgTEP1 in pathogen opsonization and elimination, discussing their interaction networks with co-factors such as LRIM1/APL1C, BgFREPs and Biomphalysin. Furthermore, we analyze differences in immune pathways mediated by TEPs, including reactive oxygen species (ROS) generation, phagocytic elimination, and melanization responses, as well as their regulatory mechanisms governed by host genetic backgrounds and environmental factors. The review also evaluates the evolutionary roles of TEPs in host-parasite coevolution and highlights their potential application in vector intervention and disease prevention strategies. By elucidating both conserved and species-specific characteristics of the TEP system in these evolutionarily distant invertebrates, this work provides critical insights into the evolutionary trajectories of invertebrate innate immunity and advances theoretical frameworks for novel vector control approaches.